2020
DOI: 10.3390/pathogens9110902
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimeric G-Protein Signalers and RGSs in Aspergillus fumigatus

Abstract: The heterotrimeric G-protein (G-protein) signaling pathway is one of the most important signaling pathways that transmit external signals into the inside of the cell, triggering appropriate biological responses. The external signals are sensed by various G-protein-coupled receptors (GPCRs) and transmitted into G-proteins consisting of the α, β, and γ subunits. Regulators of G-protein signaling (RGSs) are the key controllers of G-protein signaling pathways. GPCRs, G-proteins, and RGSs are the primary upstream c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…T. fuciformis, an edible jelly mushroom, has the capacity to perform this type of morphogenesis (Zhu et al 2016). It has been demonstrated that G proteins are key regulators of this morphological transition in many dimorphic fungi (Park et al 2020). However, G proteins and their functions that are involved in T. fuciformis have been little known.…”
Section: Discussionmentioning
confidence: 99%
“…T. fuciformis, an edible jelly mushroom, has the capacity to perform this type of morphogenesis (Zhu et al 2016). It has been demonstrated that G proteins are key regulators of this morphological transition in many dimorphic fungi (Park et al 2020). However, G proteins and their functions that are involved in T. fuciformis have been little known.…”
Section: Discussionmentioning
confidence: 99%
“…AoFlbA was significantly downregulated compared to 0 h (4.4-, 5.2-, and 8.2-fold at 12, 24, and 36 h, respectively), especially in the later infection stage (Figure 1c). Meanwhile, AoRgsA, AoRgsB, and AoRgsB2-2 were also downregulated at three time points (12,24, and 36 h). In contrast, AoRgsB2-3 and AoRgsC were significantly upregulated at 12, 24, and 36 h. Specifically, AoRgsB2-3 increased by 2.8-3.0 fold at 12, 24, and 36 h, respectively.…”
Section: Expression Of Seven Rgs-encoding Genes During Trap Formation and Predationmentioning
confidence: 92%
“…The GPA activity accelerates GTP hydrolysis at the Gα subunit, thereby limiting the intensity and duration of G protein activation and inactivating or terminating downstream signals [ 10 , 11 ]. GPCRs, G proteins, and RGSs are the key components of G protein signaling and highly conserved in most filamentous fungi [ 1 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations